2022
DOI: 10.1039/d1gc03592d
|View full text |Cite
|
Sign up to set email alerts
|

Integrating lignin depolymerization with microbial funneling processes using agronomically relevant feedstocks

Abstract: This work shows the integration of reductive lignin depolymerization and microbial funneling with Novosphingobium aromaticivorans to produce 2-pyrone-4,6-dicarboxylic acid (PDC) in a lignocellulosic biorefinery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 69 publications
0
19
0
Order By: Relevance
“…In this regard, a recent study of PDC production from lignin that was depolymerized by hydrogenolysis reported PDC yields from WT poplar and sorghum of 0.8% w/w and 0.6% w/w, respectively (Perez et al, 2022). Moreover, in planta production of PDC in engineered Arabidopsis showed 3% w/w accumulation in the biomass (Lin et al, 2021), which is lower than the ~5% yield that was obtained from the Arabidopsis QsuB line 2 (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this regard, a recent study of PDC production from lignin that was depolymerized by hydrogenolysis reported PDC yields from WT poplar and sorghum of 0.8% w/w and 0.6% w/w, respectively (Perez et al, 2022). Moreover, in planta production of PDC in engineered Arabidopsis showed 3% w/w accumulation in the biomass (Lin et al, 2021), which is lower than the ~5% yield that was obtained from the Arabidopsis QsuB line 2 (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…Having established that aromatics in the APL are present as free and conjugated phenolics, we evaluated the possibility of microbially converting these aromatics to higher-value products. For this, we tested the production of PDC from APL using the engineered N. aromaticivorans PDC strain that funnels a variety of plant-derived phenolics to PDC (Perez et al, 2019;Linz et al, 2021;Perez et al, 2022).…”
Section: Quantification Of Phenolics In Apl From Wt and Qsub Sorghummentioning
confidence: 99%
See 3 more Smart Citations